High-Resolution Pseudorandom Encoder with Parallel Code Reading - Denić, D.; Ranđelović, I.; Rančić, M. (Elektronika ir Elektrotechnika, 2004)
This paper considers pseudorandom encoder as a new type of absolute encoder with only one code track. It is provided using an especial code technique based on pseudorandom binary sequences. A method for parallel reading of pseudorandom code using linear photodetector array is proposed. The presented solution considerably decreases the basic problem, which is a substantial time needed for the execution of the position measuring. The process of determining the fine and rough position is being divided based on the recorded pseudorandom code, and now, all known pseudorandom/natural code conversion methods can be directly applied, which results in 10 times measurement time reduction in relation to the already known solutions and methods in this field. Ill. 4, bibl. 11 (in English; summaries in Lithuanian, English and Russian).